Four new species of Cerambycidae (Coleoptera) from Bolivia and Brazil - Galileo, Maria Helena M.; Martins, Ubirajara R.; Santos-Silva, Antonio (Zootaxa, 2015)
Four new species of Cerambycidae are described: Sphaerion iuasanga (Elaphidiini), Glypthaga arena, Hypsioma albosericea (Onciderini) from Bolivia (Santa Cruz), and Hesycha jataiensis (Onciderini) from Brazil.